Professor V.G. Shlopov – an outstanding representative of domestic pathological anatomy (to the 80th birthday) - Zerbino , D.D.; Chaikovskyi , Yu.B.; Chernii, V.I.; Sviatenko, T.V.; Volos, L.I.; Svystunov , I.V.; Mykhailychenko, T.Ye. (Medicni Perspektivi, 2021)
Professor V.G. Shlopov – an outstanding representative of domestic pathological anatomy (to the 80th birthday)